Fifty years of development of light measurement instrumentation. (January 2018) - Bergen, T; Young, R
Instrumentation for photometry, radiometry and colorimetry has developed significantly over the past fifty years. New measurement techniques and types of detectors as well as miniaturisation of computers and electronic hardware have fundamentally changed both the size, design and complexity of instrumentation and the way that we go about our measurement work. There has also been a significant change in mindset as the increasing need for accountability for measurement results and recognition of the role of traceability and measurement uncertainty have become more pronounced. This paper summarises the state of photometric laboratories in the 1960s and list some of the key highlights in the development of instrumentation and measurement techniques since then. It is not intended as a strict chronological account of technological invention, but a reflection of how and when these technologies were adopted and adapted to light measurements, along with accompanying key papers published in Lighting Research and Technology and associated journals over that time.